2015
DOI: 10.1021/cs501967r
|View full text |Cite
|
Sign up to set email alerts
|

Acid Strength Controlled Reaction Pathways for the Catalytic Cracking of 1-Pentene to Propene over ZSM-5

Abstract: The influence of acid strength was evaluated toward the selectivity to propene on conversion of 1-pentene. For the catalytic cracking of 1-pentene, the main reaction pathways and the molar ratio of propene to ethene (P/E ratio) were controlled by acid strength with the appropriate amount of total acid sites. The results showed that the P/E ratio increased with decreasing amounts of strong acid sites, since the activation energies of individual reaction pathways were influenced by acid strength to a different e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(50 citation statements)
references
References 46 publications
7
43
0
Order By: Relevance
“…This conclusion is in line with literature reports, which showed that only strongly acidic zeolites could crack C 5 + alkenes to light C 2 and C 3 alkenes, whereas less-acidicz eotypes favored oligomerization followed by cracking to higher alkenes. [56,57] Interestingly,M iyaji et al showedt hat 2-methyl-2butene and 1-pentene were not cracked in am onomolecular mechanism over H-SAPO-5, [75] in line with the resultspresented in Figure 5. Furthermore, Meusinger et al studied cracking of n-hexanea nd n-butane overH -MgAlPO-5, H-CoAlPO-5, and H-SAPO-5.…”
Section: Product Selectivitysupporting
confidence: 71%
“…This conclusion is in line with literature reports, which showed that only strongly acidic zeolites could crack C 5 + alkenes to light C 2 and C 3 alkenes, whereas less-acidicz eotypes favored oligomerization followed by cracking to higher alkenes. [56,57] Interestingly,M iyaji et al showedt hat 2-methyl-2butene and 1-pentene were not cracked in am onomolecular mechanism over H-SAPO-5, [75] in line with the resultspresented in Figure 5. Furthermore, Meusinger et al studied cracking of n-hexanea nd n-butane overH -MgAlPO-5, H-CoAlPO-5, and H-SAPO-5.…”
Section: Product Selectivitysupporting
confidence: 71%
“…35 This type of acidity has been reported as responsible for the direct cracking of C 5+ olefins via the classical β-scission mechanism. [36][37][38] Again, in line with the literature 29 additional Brønsted-like acid sites are generated after pretreatment of the ZrS/SAPO-34 composite with water vapor as, overall, a shift in the main desorption peak to higher temperatures is observed (see yellow spectra in Fig. 2A).…”
Section: Catalysis Science and Technology Papersupporting
confidence: 84%
“…3A). [36][37][38] As expected, after boiling, the 27 Al spectrum of the ZrS/ SAPO-34 is consistent with the fresh SAPO-34 material itself, indicating the internal rearrangement to regain Brønsted acid sites. However, 27 Al is a quadrupolar nucleus and its NMR line-shape typically suffers from residual second-order quadrupolar interactions.…”
Section: Catalysis Science and Technology Papersupporting
confidence: 79%
“…The strong acid sites prefer to crack 1-pentene to ethylene. Then, the ratio of propylene to ethylene can be controlled between 1.2 and 7.9 by adjusting the acid strength of ZSM-5 zeolite [112].…”
Section: Acidity Strengthmentioning
confidence: 99%